Efectos de la restricción del pienso y suplementación con alfalfa sobre el rendimiento productivo, características de carcasa, índices cardiacos y parámetros hematológicos del pavo criado en condiciones hipobáricas. - Paredes, M. (2021)
The effectiveness of feed access time and alfalfa supplementation in finishing commercial turkeys and under natural hypobaric conditions was studied. A 2 × 2 factorial arrangement of treatments was used to assess the main effects of time of access to feed (12 and 24 h/d) and supplementation with alfalfa (0 and 1% of body weight). Additionally, the sex factor was considered to analyse the data of carcass characteristics, cardiac indices and haematological parameters. A total of 256 70-day-old Hybrid Converter turkeys were assigned to four treatments, each with four replications (8 males and 8 females in mixed-flock). All birds received the same diets for the first 70 days of age. The treatments were 12h/d-0%, 12h/d-1%, 24h/d-0% and 24h/d-1%. At 91 days of age the birds were slaughtered. No interactions or differences were observed in the main effects for feed intake, but there was a greater increase in body weigh in turkeys with access to feed 12h/d. Feed conversion was better in turkeys with access to feed for 12 h/d and that did not consume alfalfa. The restriction of hours of access to the feed and the supplementation with alfalfa did not affect the carcass performance or the accumulation of abdominal fat. Alfalfa supplementation was found to prevent degenerative enlargements of the heart, right ventricle, and liver, and counteract turkey stress caused by feed restriction.